Theory of Alamin (A Formation of Universal Communication Formula) - Muhammad Aminullah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Studies of this study need to be done to understand the basic nature of communication, so that the formation of a universal communication formula. The communication formula constructed in the theory of nature, explains that communication can be done in the form of a universal relationship ,not limited to the relationship between fellow human beings. It turns out that communication can be done in the form of relationships with all the elements that exist in the Universe of the universe is based on only one aspect of the relationship can be done on the need. Relationships that are built on necessities are an absolute right for humans to survive in their lives. The methodological approach in this research is the scientific approach that is built based on the discipline of ALAMTOLOGI. The communication formulas that are awakened in natural theory based on the discipline of ALAMTOLOGI communication and applied on all aspects of human relationships with others scientifically, systematically and universally in everyday life in a harmony way. The NAMORY THEORY formula is X + Z (Y) ⤇ g Hp and X - Z (0) ⤇ g Cp. Based on this concept the implementation of communication of this formula in the implementation of communication can ensure its attainment to the value of harmony or lameness value. Good communication is harmony communication.